Bring Back the Glory : What happens when God's people pray for revival - Maxwell, Randy (Pacific Press, 2000)
All over the world, believers are beginning to cry out to God for revival--for a return of His glory into their lives, churches, and communities. Are you among them? Is the latter rain about to fall?